Elan - California State College at Hayward::::::; California State University, Hayward::::::; California State University, East Bay:::::: (1966)
1966 Elan yearbook contains individual and group portraits of faculty, administrators, and students. Photographs of gubernatorial candidate Ronald Reagan and Bishop James Pike, who spoke on campus in the spring, are also included.